The Development of Inshore Traffic Zone in Sunda Strait - Dyan Primana Sobaruddin; Armaidy Armawi; Sri Rum Giyarsih (Indonesian Journal of Geography, 2026)
This study aims to delineate spatial conflict zones, assess navigational risk, and formulate geographic information system (GIS)-based design scenarios for a proposed eastern Inshore Traffic Zone (ITZ) in Sunda Strait which is a very important section of Archipelagic Sea Lane I (ALKI I) in Indonesia. International Maritime Organization (IMO) established a western ITZ in 2020, but the eastern sector lacked a systematic nearshore traffic scheme. This is due to the coexistence of competing activities such as fisheries, conservation zones, port access routes, and submarine infrastructure in a limited coastal corridor. Therefore, a spatially integrated method was adopted and combined with Automatic Identification System (AIS)-derived traffic density, longitudinal Vessel Traffic Services (VTS) deviation data, hydrographic maps, and Banten marine spatial planning (RZWP3K) layers in GIS overlay framework. AIS measurements showed that ferry crossings of 2,691–3,168 per month were significantly higher than the longitudinal Traffic Separation Scheme (TSS) flows reported as 365–576 per month and led to frequent crossing encounters in nearshore multi-use areas. The kernel density analysis also signaled that the interactions were concentrated east of TSS corridor specifically in Merak–Cigading waters and Sangiang Island. The two ITZ design possibilities assessed were the complete segregation model and a corridor-oriented layout. The corridor-based ITZ had enhanced spatial compatibility by reducing the overlap between reserve areas and underwater cable routes while augmenting navigational safety. The results showed that GIS-enabled spatial governance could improve traffic management by restructuring movement patterns rather than limiting navigation. This further led to the incorporation of navigational safety goals into maritime spatial planning across intricate archipelagic rivers.